ERA REVOLUSI INDUSTRI 4.0: TANTANGAN DAN PELUANG DALAM UPAYA MENINGKATKAN LITERASI PENDIDIKAN - Yusnaini, Yusnaini; Slamet, Slamet (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
In industrial revolution 4.0 maneuvers will produce a "smart factory" with a modular structure, the physical-cyber system will supervise physical processes, create copies of the physical world virtually, and make decisions that are not centralized. Through the internet for everything, cyber-physical systems communicate and cooperate with each other and humans together. Through cloud computers internet and cross-organization services are provided and utilized by various parties in the value chain. With this speed a new breakthrough occurred in the present era, on an exponential scale, not on a linear scale; Second, the decline in marginal production costs and the emergence of platforms that can unite and concentrate several scientific fields that have been proven to increase employment output. Transformation can cause changes in the entire system of production, management, and governance of an institution; and, thirdly, this global revolution will have a major influence and be formed in almost all countries in the world, where the scope of transformation takes place in every industrial field and can have a comprehensive impact in many places.